Produção e caracterização da surfactina de Bacillus velezensis H2O-1 e suas diferentes aplicações na indústria do petróleo - Guimarães, Carolina Reis (2019)
Biosurfactants are molecules with surfactant properties produced by microorganisms, which can be used in several industrial fields, such as in the petroleum industry, where they can be used to aid the oil extraction and to control biocorrosion. One of the most studied and efficient biosurfactants is surfactin, a lipopeptide produced by several species of Bacillus. Unlike chemical surfactants, which are usually produced from petroleum hydrocarbons, toxic and difficult to degrade in the environment, biosurfactants are biodegradable and often more effective than surfactants. The objective of this study was to produce and to characterize the surfactin produced by B. velezensis H2O-1, as well as to evaluate the potential of this molecule for use in the Microbial Enhanced Oil Recovery (MEOR) and in the control of biocorrosion. B. velezensis H2O-1 produces five surfactin homologs that differ in the length of the fatty acid chain. These homologs were stable to variations in temperature, pH and ionic strength, having high emulsification and dispersion power of different types (APIs) of petroleum. For use in MEOR, the surfactin inverted 100% of the wettability of calcite impregnated with petroleum. In addition, the crude extract containing the surfactant maintained its excellent interfacial properties when subjected to the extreme conditions of pressure, temperature and salinity found in the post-salt (70 °C, 70 g/L and 27.58 MPa) and pre-salt layers (100 °C, 150 g/L and 48.2 MPa). In order to verify the efficacy of the biosurfactant in the control of biocorrosion, it was observed inhibition of the biofilm formation on the conditioned surfaces (carbon steel coupons) in reactors with presence of microorganisms present in the water of production. Surface conditioning with surfactin change the cupons hydrophobicity, leaving them less hydrophobic. Moreover, this treatment reduced the biofilm formation and, consequently, reduced biocorrosion. In addition, this surfactant presented low toxicity against Artemia salina, being considered safe for environmental application. These results indicate an excellent application potential of these surfactins for use in MEOR and in the control of biocorrosion in metallic surfaces.